Safety and efficacy of DSP® (Na2EDTA, tannin‐rich extract of Castanea sativa, thyme oil and origanum oil) for pigs for fattening - Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; Pechová, Alena; et al. (EFSA journal, 2020)
Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety for the environment and efficacy of DSP® (a mixture of disodium salt of ethylenediaminetetraacetic acid (Na2EDTA), tannin‐rich extract of Castanea sativa, thyme oil and origanum oil) as a zootechnical feed additive for pigs for fattening. The European Commission request followed an inconclusive opinion of the FEEDAP Panel published in 2016. The applicant submitted additional information to allow the FEEDAP Panel to complete its assessment; these additional data, related to the safety for the environment and the efficacy of the additive, were the subject of this opinion. Concerning safety for the environment, the risk quotient (PEC/PNEC) value for aquatic organisms was < 1, indicating no concerns of DSP® for the aquatic compartment; no toxicity data for terrestrial organisms were provided and consequently no conclusion on the safety of DSP® for the terrestrial compartment could be reached, as well as on the risk for groundwater contamination. Based on the results from three studies in pigs for fattening in which final body weight and average daily weight gain were increased, and feed to gain ratio was improved, the FEEDAP Panel concluded that DSP® has the potential to be efficacious as a zootechnical additive in pigs for fattening.